28. KNOWLEDGE AND PRATICE OF PREVENTIVE OF CHRONIC OBSTRUCTION PULMONARY DISEASE OF PEOPLE 40 YEARS AND OVER IN HUE CITY (Vietnam Journal of Community Medicine, 2025)
Objective: To decrible knowledge and practice of chronic obstructive pulmonary disease prevention and learn some related factors of people aged 40 years and older in Hue city.Subjecs and Method: Cross-sectional descriptive study was conducted on 420 people who was  40 years old and older in Hue city.Results: The proportion of study subjects with satisfactory knowledge about chronic obstructive pulmonary disease was 23.6%; Of the study subjects who did not have adequate knowledge about chronic obstructive pulmonary disease, 76.4%. 18.6% of study subjects had satisfactory practices in preventing chronic obstructive pulmonary disease; The study subjects did not have any practice in preventing chronic obstructive pulmonary disease, which was 81.4%. Factors related to knowledge about chronic obstructive pulmonary disease: occupation, education level. Factors related to chronic obstructive pulmonary disease preventive practices:  are group, occupation and knowledge about chronic obstructive pulmonary disease.
Keywords: Knowledge; practice; cchronic obstructive pulmonary disease